Generation and control of ultrafast pulse trains for quasi-phase-matching high-harmonic generation - Robinson, T; O'Keeffe, K; Zepf, M; Dromey, B; Hooker, S (Optical Society of American (OSA), 2010)
Two techniques are demonstrated to produce ultrashort pulse trains capable of quasi-phase-matching highharmonic generation. The first technique makes use of an array of birefringent crystals and is shown to generate high-contrast pulse trains with constant pulse spacing. The second technique employs a grating-pair stretcher, a multiple-order wave plate, and a linear polarizer. Trains of up to 100 pulses are demonstrated with this technique, with almost constant inter-pulse separation. It is shown that arbitrary pulse separation can be achieved by introducing the appropriate dispersion. This principle is demonstrated by using an acousto-optic programmable dispersive filter to introduce third- and fourth-order dispersions leading to a linear and quadratic variation of the separation of pulses through the train. Chirped-pulse trains of this type may be used to quasi-phase-match high-harmonic generation in situations where the coherence length varies through the medium. © 2010 Optical Society of America.